Three Arabic Treatises on Aristotle's Rhetoric : The Commentaries of Al-Farabi, Avicenna, and Averroes - Ezzaher, Lahcen Elyazghi (Landmarks in Rhetoric and Public Address Ser, 2015)
Cover -- Title Page -- Copyright -- Contents -- Acknowledgments -- Introduction -- 1. Al-Fārābī's Book of Rhetoric -- 2. Avicenna's Compendium, or Al-cArūdī's Philosophical Treatise on the Meanings of the Book of Rhetoric -- 3. Averroes's Middle Commentary on the Book of Rhetoric (Book I) -- Conclusion -- Bibliography -- Index -- Author Biography -- Landmarks in Rhetoric and Public Address, also in this series -- Back Cover.